2003
DOI: 10.1007/s00134-002-1548-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled mechanical ventilation on respiratory muscle contractile properties in rabbits

Abstract: Mechanical ventilation in rabbits produces alterations in contractile properties of the diaphragm and 5th external intercostal muscle, increases both muscles fatigue, and promotes atrophy of type II fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 34 publications
4
61
0
7
Order By: Relevance
“…Importantly, these results suggest that the MV-induced diaphragm contractile dysfunction occurs at the level of the peripheral muscle (91). Indeed, numerous animal studies consistently report that prolonged MV results in a rapid and time-dependent decrease in diaphragmatic specific force production measured in vitro using electrical stimulation of diaphragmatic muscle strips (9,16,19,33,35,56,87,93,98). A recent report suggests that as few as 6 h of MV results in diaphragmatic contractile dysfunction in mice (73).…”
Section: Mv-induced Diaphragmatic Contractile Dysfunctionmentioning
confidence: 87%
See 2 more Smart Citations
“…Importantly, these results suggest that the MV-induced diaphragm contractile dysfunction occurs at the level of the peripheral muscle (91). Indeed, numerous animal studies consistently report that prolonged MV results in a rapid and time-dependent decrease in diaphragmatic specific force production measured in vitro using electrical stimulation of diaphragmatic muscle strips (9,16,19,33,35,56,87,93,98). A recent report suggests that as few as 6 h of MV results in diaphragmatic contractile dysfunction in mice (73).…”
Section: Mv-induced Diaphragmatic Contractile Dysfunctionmentioning
confidence: 87%
“…This primate study concluded that prolonged MV results in significant impairment of diaphragmatic contractile performance as indicated by a decrease in both maximal transdiaphragmatic pressure and diaphragmatic endurance (6). Following these early investigations, scientific interest in the effects of MV on diaphragm structure and function grew rapidly, and numerous animal studies published in 2002-2003 consistently concluded that prolonged MV results in the rapid development of both diaphragmatic atrophy and contractile dysfunction (16,19,33,91,93,98,100). Mechanistic studies into the cell signaling events responsible for VIDD began in 2003 when investigations revealed that prolonged MV results in diaphragmatic oxidative stress and that oxidant damage in the diaphragm is a requirement for VIDD (9,119).…”
Section: Ventilator-induced Diaphragm Dysfunction: Historical Overviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies demonstrated the following alterations in the diaphragm after controlled mechanical ventilation: reduced muscle mass 2,10,11 ; diminished type I, IIa, and IIx/b fiber dimensions 3,12,13 ; myofibrillar damage 4 ; enhanced proteolysis 12 ; increased protein oxidation and lipid peroxidation 14 ; reduced expression of the insulin-like growth factor (IGF-I) 3 ; decreased sarcoplasmic/endoplasmic reticulum Ca 2+ -ATPase (SERCA-1a) expression 15 ; increased expression of muscle atrophy factor (MAF-box) 16 ; and a decrease in myonuclear content 17 . All of these factors seem to contribute to the development of VIDD, but the precise contribution of each factor and their apparition kinetics has yet to be defined.…”
Section: Ventilator-induced Diaphragmatic Dysfunction (Vidd)mentioning
confidence: 99%
“…Controlled mechanical ventilation induces diaphragm muscle atrophy [10][11][12][13] . VIDD develops rapidly, as early as 12 h after the institution of CMV 17 , and is more pronounced in the diaphragm, which atrophies earlier than the peripheral skeletal muscles that are also inactive during CMV [10][11][12] .…”
Section: Muscle Atrophymentioning
confidence: 99%